Risks of suicide in migraine, non-migraine headache, back, and neck pain: a systematic review and meta-analysis - Giakas, Alec; Mangold, Kiersten; Androulakis, Anthony; Hyduke, Noah; Galynker, Igor; Thiam, Melinda; Cai, Guoshuai; Androulakis, X. Michelle (Frontiers in Neurology, 2023)
Objective: To conduct a systematic review and meta-analysis on suicide ideation, attempts, and death in patients with head, neck, and back pain. Method: Search was performed using PubMed, Embase, and Web of Science from the date of the first available article through September 31, 2021. A random effects model was used to estimate the pooled odds ratios (ORs) and 95% confidence intervals (95% CI) for the association between suicidal ideation and/or attempt and head, back/neck pain conditions. Articles describing non-migraine headache disorders and death by suicide were also reviewed but were not included in the meta-analysis due to an insufficient number of studies. Results: A total of 20 studies met criteria for systemic review. A total of 186,123 migraine patients and 135,790 of neck/back pain patients from 11 studies were included in the meta-analysis. The meta-analysis showed that the estimated risk of combined suicidal ideation and attempt in migraine [OR 2.49; 95%CI: 2.15-2.89] is higher than that in neck/back pain [OR 2.00; 95%CI: 1.63-2.45] compared to non-pain control groups. Risk of suicide ideation/planning is two folds higher [OR: 2.03; 95%CI: 1.92-2.16] and risk of suicide attempt is more than three folds higher [OR: 3.47; 95%CI: 2.68-4.49] in migraine as compared to healthy controls. Conclusions: There is an elevated risk of suicide ideation and attempt in both migraine and neck/back pain patients in comparison to healthy controls, and this risk is particularly higher among migraine patients. This study underscores the critical needs for suicide prevention in migraine patients.